Testing Contract Theory: A Survey of Some Recent Work - Pierre André Chiappori; Bernard Salanié (Center for Economic Studies and ifo Institute (CESifo), 2002)
While the theoretical literature on contracts has been enormous since the seventies, empirical tests of the theory have long remained scarce. However, new empirical work has been developed in the last ten years that sheds light on the empirical validation of the theory. This paper aims at surveying the recent empirical work on contracts. The focus throughout is on the need to properly account for unobserved heterogeneity.
Keywords: 330